Strategi Penguatan Nilai Spiritual dalam Meningkatkan Child Well-Being Anak Usia Dini di Era Digital - Risma Nadhitul Izmah; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to analyze strategies for strengthening spiritual values in improving child well-being in early childhood in the digital era. This research uses a qualitative approach through a literature review by examining relevant scientific articles, books, and reports published in the last ten years. The results show that excessive use of digital technology can negatively affect children's emotional and social development, including reduced social interaction and emotional regulation (Twenge & Campbell, 2018). Strengthening spiritual values such as religious habituation, moral education, and emotional awareness can improve children's well-being by fostering emotional stability, positive behavior, and a sense of security (Pandya, 2018). In addition, collaboration between family and educational institutions plays a significant role in implementing spiritual values effectively. Therefore, structured spiritual-based educational strategies are recommended to support children's holistic development in the digital age